Current status and influencing factors of enteral nutrition interruption among critical patients: a systematic review - Lu, Xiaoyan; Wang, Xin; Yu, Weixia; Cai, Jianzheng; Wang, Yuyu; Cao, Yongzhi; Dan, Limi; Wang, Qingling (Frontiers in Nutrition, 2025)
PurposeThis study systematically reviewed and elucidated the current status and key determinants of enteral nutrition interruption (ENI) in critically ill patients. By shedding light on these factors, we aimed to furnish compelling evidence to mitigate the occurrence of ENI in this critical setting.MethodsWe embarked on a comprehensive search across seven prominent databases, PubMed, Embase, Web of Science, Cochrane Library, Scopus, EBSCO, and Ovid Medline, spanning from their inception to 27 May 2024. Two independent researchers meticulously screened and assessed the quality of the literature, extracting data on the current status and influencing factors of ENI. This rigorous approach culminated in a descriptive systematic review and analysis.ResultsFrom an initial pool of 2,984 studies, 28 were deemed suitable for inclusion in this review, comprising 20 cross-sectional and eight cohort studies. Moreover, 16 studies highlighted ENI incidence rates ranging from 4.7% to a staggering 100%, with an overall average of 48.3%. Among 17 studies, a total of 4,890 ENI episodes were reported involving 2,008 critically ill patients, translating to an average of 2–3 episodes per patient. Four studies detailed the cumulative ENI duration in 327 critically ill patients, totaling 11037.2 h, with an individual average of 33.8 h per patient. The analysis revealed four primary factors influencing ENI: procedures, gastrointestinal events, feeding tube problems, and hemodynamic instability. Procedures accounted for 29.8%–85.0% of ENI frequency and 34.6%–81.2% of duration, with averages of 63.4% and 52.1%, respectively. Gastrointestinal events contributed to 9.4%–59.7% of ENI frequency and 11.5%–21.4% of duration, averaging 19.2% and 18.1%. Feeding tube problems ranged from 0.9% to 29.3% in frequency and 1.3%–25.6% in duration, with averages of 9.3% and 11.6%. Hemodynamic instability was responsible for 0.9%–20.0% of ENI frequency and 1.1%–5.1% of duration, averaging 3.9% and 2.6%.ConclusionThe incidence and frequency of ENI in critically ill patients are notably high, with interruptions lasting for extended durations. The primary culprits, procedures, gastrointestinal events, feeding tube problems, and hemodynamic instability, influenced ENI occurrence.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_recordphp?ID=CRD42024554417, identifier CRD42024554417.